Agricultural-based curriculum: A comparative study - Abd Ghani, A.; Rithuwan, H.; Abdullah, M.; Ismail, S.M. (2008)
This paper will report and propose an agricultural based curriculum and to build an agricultural based school in Malaysia. Data were collected by document analysis from four schools; i.e., Ohio; United States; Agricultural High School, Sydney, Australia; Farm School, Massachusets; and Agricultural School, Cerrito, Paraguay. The information gained was analyzed by comparative document analysis. The strengths and weaknesses were reviewed and the analysis shows that the curriculum and programs implemented in those schools are suitable for implementation in our school. In aspect with new agriculture skills, this study demonstrates that the contents of the subjects are applicable, adequatel, and fulfill the school learning's requirements and environment here in Malaysia. This study indicated that student will gain new practical practices and knowledge in order to boost up their new skills and techniques as preparation for further academic learning. Furthermore,our country has various advantages such as climate, weather, rain and also unexplored land. Our findings revealed that the curriculum from the above mentioned schools can be implemented here with some improvisation in the existing curriculum. In addition we also proposed a fully agricultural based school curriculum which can be used for the ministry and the beneficial stakeholders. We hope the findings in this analysis would lead to a new paradigm shift towards agricultural curriculum in our country.